Pigeon Pea (Cajanus cajan) Seed Meal as Protein Source for Pullets: 1. Performance of Grower Pullets Fed Raw or Processed Pigeon Pea Seed Meal Diets - Amaefule, K.U.; Ironkwe, M.C.; Ojewola, G.S. (International Journal of Poultry Science, 2005)
The experiment was conducted with 150 nine week-old black Bovan Nera pullets to evaluate the performance of grower pullets fed raw or processed pigeon pea seed meal (PSM) diets from the grower (9th week) stage of life. The experiment, which was in a completely randomized design (CRD), comprised pullets fed 20% PSM diets that were isoenergetic and isonitrogenous. The seeds were used as raw, boiled for 30 minutes, toasted for 30 minutes or soaked in water for 24 hours. Each treatment (raw, boiled, toasted, soaked or control diets) was replicated three times. Parameters measured were feed intake, weight gain, feed conversion ratio, live weight at point of lay and feed cost. Pullets fed 20% boiled PSM diet had significantly higher (P< 0.05) daily protein intake and live weight at point of lay. It was concluded that PSM could be a good protein source for grower pullets, which could be incorporated into the diets at 20% of the whole diet without any adverse effect on growth performance.